The Practicality of E-Module Indonesian Language Based on Contextual for Students of Elementary School Teacher Education - Wahyuni, Fitri; Munirah, Munirah; Nurlina, Nurlina (PPSDP International Journal of Education, 2024)
This study aims to analyze the practicality of the Indonesian language E-Module of based on contextual for Elementary School Teacher Education students of Muhammadiyah University of Makassar in the learning process. The method used in this study is a type of research & development research using the 4-D (Four-D) development model, which consists of 4 stages of development, namely define, design, development, and disseminate. With a research sample of 50 Elementary School Teacher Education students and 3 samples of lecturers at Muhammadiyah University of Makassar. Data collection techniques using lecturer response questionnaires and student response questionnaires. The data analysis technique used in this study is descriptive analysis. Based on the results of the study, it shows that the implementation of the Indonesian language E-module for general basic courses based on contextual practice is used, this can be seen based on the results of the lecturer response questionnaire with an average value of 100%, 92%, 83% with the category of very practical, and student responses with an average value of 85%, 86%, 88%, 89%, and 91% with the category of very practical. So, it can be concluded that by implementing the Indonesian language E-module for general basic courses based on contextual practice for students, it is very practical to use in the learning process.